More effective professional development can help 4-H volunteers address need for youth scientific literacy - Martin H. Smith; Lynn Schmitt-McQuitty (California Agriculture, 2013)
Professional development models that involve communities of practice have been shown to be effective to help meet the professional development needs of 4-H volunteers who implement science programming with youth.

Beyond evaluation: Findings from the California 4-H camp study - Lynn Schmitt-McQuitty; California 4-H Camp Evaluation Team (University of California, Division of Ag and Natural Resources, 2007)
Report describes the findings from a two year study. Using a framework of positive youth development supports and opportunities (Connell & Gambone, 2002), the study explored whether young people, both teens and campers, experienced supportive relationships, safety, youth involvement and skill building at camp. The study also explored components of environmental stewardshhip at 4-H camp. Focus groups were conducted with campers, teen staff and adults. Findings revealed that there was significant change in camper's responsed of certain supports and opportunities in the two camps that implemented their improvement plans. Based on the findings, the report provides suggestions for making change, including a sample camp improvement action plan.
Also in Research you may have missed, published by University of California

The development and evaluation of experiential learning workshops for 4-H volunteers - Richard P. Enfield; Lynn Schmitt-McQuitty; Martin H. Smith (2007)